多元閱讀策略教學對摘要與閱讀理解能力效果之研究 The Effectiveness of Multiple Reading Strategy Instructions on Summarizing Ability and Reading Comprehension - 劉佩雲 Pei-Yun Liu (National Changhua University of Education, 2019)
閱讀理解是從文本中擷取重要訊息，進而理解、詮釋並應用的能力，也是素養學習的基礎。本研究整合預測、提問、摘要與文章結構等多元閱讀策略，期以結構化的階段性教學融入國語文領域，進行課文本位的多元閱讀策略教學，循序培養學生的摘要及閱讀理解能力。研究採準實驗研究法不等組前後測設計，以東部地區一個國小常態分班的兩班五年級學生為對象，進行一學期18 週的教學實驗。研究以教學實驗處理為自變項，以摘要測驗及閱讀理解的後測為依變項，以摘要測驗及閱讀理解的前測為共變項，進行單因子共變數分析。結果發現實驗組摘要測驗及閱讀理解表現上，均優於對照組，顯示多元閱讀策略教學能有效提升學生的摘要與閱讀理解能力。 Reading comprehension is the capability of retrieving important data from text and further understanding, interpreting, and applying such data. Reading competence is fundamental to the learning of all academic subjects in school. The multiple reading strategy instructions this research adopts integrate the forms of predicting, questioning, summarizing, and text structure. This study employs the quasi-experimental non-equivalent pre-test/post-test design with the aim at practically building students' summarizing and reading comprehension abilities via structured and procedural multiple reading instructions of a Chinese textbook. The subjects of this study comprise two normally grouped 5th grade classes in eastern Taiwan. The independent variable is the experimental instruction treatment, the dependent variables are summarizing posttest and reading comprehension, and the co-variables are summarizing pre-test and reading comprehension pre-test. The data are processed by one-way ANCOVA. The findings indicate that the experiment group performs better than the control group in both the summarizing test and reading comprehension test. This result demonstrates that multiple reading strategy instructions effectively enhance both reading summarizing and comprehension abilities.